FLOOD MANAGEMENT STRATEGY IN THE SINGKAWANG CITY USING SWOT ANALYSIS - Nathaniel, Yose Gerard; Soeryamassoeka, SB.; Yulianto, Eko (Fakultas Teknik Universitas Tanjungpura, 2023)
Singkawang City is a coastal city surrounded by mountains with an area of 504 km2. The Singkawang City area often experiences flooding, which gets worse every year. A deeper analysis is needed to determine strategic issues and flood management strategies in Singkawang City. This study analyzes flood control strategies and what mitigation is proper for Singkawang City. The results of this analysis are then used as a guide for stakeholders in making the best decisions to deal with floods in Singkawang City.To identify strategic issues regarding flooding, a Focus Group Discussion (FGD) on flood issues in Singkawang City was held on 21 June 2023, which credible stakeholders attended. The results of the FGD mapped out which factors are Strengths, Weaknesses, Opportunities, and Threats. Then, an IFAS and EFAS analysis is carried out to determine the most influential flood control strategy, which will be carried out by AHP analysis to determine the most priority strategy to implement. After that, the strategy timeframe was obtained using SFAS analysis for the short-term, medium-term, and long-term. This strategy is then complemented by disaster mitigation before, during, and after the flood.The analysis results show that the right strategy for flood management in Singkawang City in an integrated manner is the W-O Strategy, namely, improving the weaknesses in Singkawang City so that the existing opportunities can be maximized. The strategy with the highest priority from the AHP analysis is that the government can formulate a strategy for structuring the Singkawang River corridor with a weight of 0.247 and a score of 2.23. As well as getting flood mitigation for before, during, and after the flood.